Exploitation status and food preference of adult tropical horseshoe crab, Tachypleus gigas - Mohd Razali bin Md Razak (Kulliyyah of Science, International Islamic University Malaysia, 2018)
According to this study, local in Malacca more preferred to apply the modern method (fishing net) (65.85%) than traditional method (hand-harvest) (34.15%) to harvest the T. gigas from the wild (p<0.05), while locals in Pahang more preferred to apply traditional (56.1%) than modern method (43.9%). Frequency of the modern harvesting method application in Malacca (25 ± 10.48 times) was higher than the traditional method (2 ± 0.73 times) and also higher compared to the modern method application in Pahang (6 ± 3.45 times) (p<0.05). Quantity of harvested crabs per month for one individual was higher in Malacca (16,860 T. gigas) compared to Pahang (4,180 T. gigas). Foods conditions would substantially influence their edibility. However, horseshoe crabs might have specific behaviour to manipulate the edibility of the foraged food. A total of 30 males and 30 females were introduced with five different natural potential feeds, namely, gastropods (Turritella sp.), crustacean (Squilla sp.), fish (Lates calcarifer), bivalve (Meretrix meretrix) and polychaete (Nereis sp.). The conditions of introduced feeds had been manipulated based on the natural foods condition in nature; decayed and protected in shell, hardened outer skin and host-tubed. Female crabs took shorter response period (3.42 ± 2.42 min) toward surrounding food compared to males (13.14 ± 6.21 min). Horseshoe crabs showed preference toward unshelled gastropods. The preference percentage of female (50%) toward unshelled gastropods was higher than males (36.67%). There is no preference behaviour showed by T. gigas on the shelled, hardened outer skin and host-tubed feed. Only the female crabs showed rejection toward decayed food. Different population of horseshoe crabs might have different food preferences. Stomach contents analyses were conducted on 60 samples of male and female; 10 males and 10 females were trapped in fishing net during the incoming high tide and 20 males and 20 females were hand-harvested at the spawning beach (10 samples during pre-mating and 10 during post-mating). This study found that echinoderm served as a main food composition in the gut of males (50%) and females (51.94%) during the open sea migration phase. The main composition was substituted by macrophyte (males: 59.51% to 65.15%; females: 36.36% to 58.10%) as they arrived to the spawning area. Based on Electivity Index, male crabs showed positive preference toward polychaete (EI: 0.04) and macrophyte (EI: 0.19) at the spawning site while, the females showed positive preference toward bivalve (EI: 0.46). In this study, 30 males and 30 females were introduced with gastropod, crustacean and bivalve in different percentage (0.2%, 0.6%, 1.0%, 1.4%, 1.8%, and 2.2%) that expressed from horseshoe crabs body mass to determine the level of the satiation. After being harvested from the wild, male crabs did not significantly eat until two weeks in captivity while, females (51.43% ± 25.54) started to eat during the early first week. Two-way ANOVA study found that females T. gigas' satiation levels (crustacean: 1.7% ± 0.08; bivalve: 1.8% ± 0.06; gastropods: 1.8% ± 0.04) were significantly higher than males (crustacean: 1.4% ± 0.02; bivalve: 1.6% ± 0.05; gastropods: 1.7% ± 0.08) for all feed types (F = 13.98, p<0.05). Gut transit times of males (crustacean: 17 ± 1.7 hrs; bivalve: 17 ± 1.7 hrs; gastropods: 23 ± 4.6 hrs) were significantly longer than females (crustacean: 10 hrs ± 1.7; bivalve: 12 hrs ± 0; gastropods: 19 hrs ± 1.7)(F = 3.72, p<0.05). Male crabs took shorter time (1 ± 0 hr) to achieve their satiation compared to female crabs (2 ± 0 hrs).